Optimizing Indonesian MSME Financial Management Through Blockchain Technology Integration: Feasibility Study, Transparency, and Implementation Challenges - Aria Dian Tri Wahyuni; Agilistya Rahayu; Dimas Indra Laksmana (Journal of Innovative and Creativity, 2026)
Financial management of MSMEs in Indonesia still faces various fundamental weakness, especially in the aspects of recording, reporting, separation of personal and business finances, and transparency which have a negative impact on credibility and access to capital. The study purpose was blockchain technology has emerged as an alternative solution that is conceptuallty capable of increasing transparency, accountability, data security, and efficiency of financial processes through permanent transaction recording and the use of smart contracts. Materials and methods. This research will employ a qualitative approach supported by descriptive quantitative data. The research design will be both exploratory and descriptive. The qualitative approach will be used to deeply understand the perceptions, experiences, and challenges faced by MSMEs, as well as expert perspectives regarding blockchain integration in financial management. Meanwhile, descriptive quantitative data will be used to provide an overview or level of readiness regarding specific aspects of the feasibility study.Results. Based on technical, economic, operational, and legal and regulatory feasibility analyses, blockchain integration is considered potential but cannot be implemented directly without adapting to infrastructure limitations, costs, human resource competencies, and evolving regulatory certainty. Challenges such as limited resources, low digital literacy, technological complexity, and data protection issues require a structured mitigation strategy through affordable service models, increased capacity of MSMEs, government policy support, and system design that maintains a balance between transparency and privacy.Conclusions. This research confirms that blockchain integration in MSME financial management is not simply a technology adoption agenda, but part of a strategic effort to build a more inclusive, credible, and sustainable digital financial ecosystem. Its successful implementation depends heavily on collaboration between MSMEs, the government, financial institutions, and technology developers in designing solutions that meet the characteristics and real needs of MSMEs in Indonesia.